(untitled) (Research, Society and Development, 2022)
This study permeates the context of remote teaching and Digital Information and Communication Technologies (TDIC) in the context of the Covid-19 pandemic in the State of Ceará, however, we elucidate some notes based on the educational scenario of public schools, to which we adhere as locus for data collection was Colégio Liceu do Ceará. Indeed, the research was developed in a qualitative-quantitative methodological proposal. Therefore, we merged this hybrid way of analyzing and interpreting the data in this work, with the selection and analysis of official documents from the government of the State of Ceará, and a free interview with (Manager 1 and 2). And, in addition to this, we list documents inherent to the researched school, in which we explain a minute of the second half of 2020 meeting, and a calendar of school activities, for the months of September and October 2021; in addition to the assertions by Madrigal (2016), Pereira (2017), Augusto; Santos (2020), among other authors essential to the formation of the necessary foundation for the research carried out, in partnership with the Postgraduate Program in Planning and Public Policies of the UECE. In the results and discussion, accessibility to technological tools is currently a national problem, however, for the State of Ceará, like the Liceu, official documents and interviews, we perceive the uniqueness of public educational policies put into practice, in the sense of to include, to minimize structural inequalities in the social sphere, and to promote education for all, having remote/hybrid teaching as a motto in the dissemination of knowledge to the people of Ceará.